Detection of vkorc1 polymorphism: comparison of polymerase chain reaction/restriction fragment length polymorphism (pcr + rflp) with allele–specific polymerase chain reaction : Ugotavljanje VKORC1 polimorfizma: Primerjava metod verižne reakcije s polimerazo/ polimorfizma dolžin restrikcijskih fragmentov (PCR + RFLP) z alelno specifično verižno reakcijo s polimerazo - Stangler Herodež, Špela; Stankovič, Nastja; Zagradišnik, Boris; Erjavec Škerget, Alenka; Kokalj Vokač, Nadja (Acta Medico-Biotechnica, 2021)
Purpose: The VKORC1 polymorphism is an important genetic factor affecting warfarin dose requirement. Patients require different warfarin doses in order to achieve the target therapeutic anticoagulation. The aim of our study was to determine the frequency of single nucleotide polymorphisms (SNP) in the VKORC1 gene in the general population, using a simple, rapid, and economical method.Methods: For genotyping, the restriction fragment length polymorphism (RFLP) of polymerase chain reaction (PCR)–amplified DNA was used and compared to allele– specific polymerase chain reaction. We genotyped 441 DNA samples obtained from the healthy general population in North–Eastern Slovenia. Genotypes for the tested group were evaluated to determine whether the population followed the Hardy–Weinberg equilibrium. The genotypes and allele frequencies were calculated.Results: The results obtained using the allele–specific polymerase chain reaction were consistent with those obtained using the PCR + RFLP method. The G allele frequency (0.62) was higher than the A allele frequency (0.38) in the general population from North–Eastern Slovenia. Conclusions: The PCR+RFLP method involved additional manipulation of the PCR products at the expense of analysis time, consumption of reagents and equipment. The allele–specific polymerase chain reaction was a simple and rapid method for the detection of SNP in the VKORC1 gene, and is available in any laboratory with the minimum of equipment and reagents required.